Operator Training Simulator Handbook Best Practices for Developing and Investing in OTS - Philip, Joseph (Packt Publishing, Limited, 2022)
Make the most of OTS systems in operator training and engineering Key Features Learn OTS project delivery best practices from the author's 30 years of experience Explore use cases to understand how your OTS systems can maximize ROI for users Discover how to best develop OTS training models for developers and users Book Description Operator training simulators in the process industry have been around since the 1970s, but you may not find a book that documents the development of these systems and the standard best practices. The Operator Training Simulator Handbook covers best practices for OTS engineering and OTS training development and delivery, starting from the basic the jargon and the different types of OTS systems. It will take you through the best approaches to project specification as well as building, maintenance, planning, and delivering these systems by sharing real-life experiences and dos and don'ts. As you advance, you'll uncover the various challenges in the planning and delivery of operator training models and understand how to address those by working through real-world projects. This book helps in specifying the best fit for purpose, choosing a cost-effective system when acquiring an OTS. You'll also learn how you can turn your OTS projects into digital twins before finally learning all about documentation in a typical OTS project, covering the sample structure that you can use as a starting point in your projects. By the end of the book, you'll have learned best practices for developing operator training simulator systems and have a reference guide to overcome common challenges. What you will learn Become familiar with the OTS jargon to set a base for understanding OTS aspects Implement training planning methods that have been tried and tested in the industry for many years Get to grips with writing well-planned documentation for your OTS project Review new model suggestions to maximize benefits of the OTS systems and the actual ICSS control systems to maximize ROI for users Understand Cloud OTS systems as a new way to address some of the common issues that developers and users face Create digital twins of your OTS projects Who this book is for This book is for suppliers who build and deliver OTS systems, OTS buyers, or companies looking to invest in these systems. Anyone with an interest in OTS systems, including university students or graduates who will work on these systems, will find this book useful. Basic knowledge of either OTS systems, ICSS control systems, or process engineering will help you grasp the concepts covered in this book.